Front Cover: Hybrid Organic‐Inorganic Heterogeneous Interfaces for Electrocatalysis: A Theoretical Study of CO2 Reduction to C2 (ChemCatChem 4/2022). Issue 4 (27th January 2022) - Wan, Mingyu; Gu, Zhiyong; Che, Fanglin
Abstract : The Front Cover shows carbon dioxide reduction reaction (CO2 RR) to C2 (e.g., ethylene, ethanol) driven by aminothiolate self‐assembled monolayer (SAM)‐modulated copper (Cu) catalysts. In their Communication, M. Wan et al. demonstrated that aminothiolate SAM‐modulated Cu catalyst could improve the activity and selectivity of CO2 RR‐to‐C2 using DFT calculations. The amine group of SAM provides an organic active site to facilitate CO2 RR rate‐limiting steps, i.e., CO2 initial activation and carbon‐carbon coupling. The confined space effect induced by the high surface coverage of SAM tunes the binding energy of the key intermediate CO * on the inorganic Cu site, enlarges the binding energy difference between CO * and COH *, and consequently, further promotes carbon‐carbon coupling. This theoretical work guides a novel catalyst design that provides hybrid organic‐inorganic active sites, confinement effects and localized electric fields, and enables efficient CO2 RR‐to‐C2 . More information can be found in the Communication by M. Wan et al.